Empowerment of Jirak Serumpun Women Farmers Group through the Application of Aquaponic System in Vegetable Cultivation in Limited Land Area - Awalina, Rahmi; Masnarivan, Yeffi; Syukri, Daimon (Andalasian International Journal of Social and Entrepreneurial Development, 2024)
Utilizing limited land for agricultural activities in urban areas is an effective alternative solution in providing healthy food for families, while reducing household costs. Aquaponic systems, which integrate fish and plant farming in a mutually beneficial recirculating ecosystem, utilize natural bacteria to convert fish waste and feed residues into nutrients for plants. Thus, aquaponics allows plants and fish to grow together in one cycle, maximizing the use of a small area of land. This service activity aims to help the Women Farmers Group (KWT) find the right solutions and strategies in overcoming the problem of limited land. One of these efforts is the creation of an innovative device in the form of a simple aquaponics system for the Jirak Serumpun Women Farmers Group, using the Deep Flow Technique (DFT) method. The aquaponics program implemented in Mata Air Village, Padang Selatan Sub-district, Padang City, has had a positive impact on the community. This training not only provides economic and social benefits, but also offers an effective solution in utilizing narrow yards productively and economically.